MEMBANGUN KESAN REALITAS MELALUI DIMENSI EDITING DALAM FILM BERGAYA MOCKUMENTARY “SEPENGGAL KISAH BUNGA” - Dani Sahrul Hadi; Nyoman Lia Susanthi; I Made Denny Chrisna Putra (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
Mockumentary movie is a fiction movie that takes the form or look like a documentary. The form of the movie is able to simulate the style of a documentary movie to tell a form of narrative in particular. The use of the mockumentary style aims to refract between reality and non-reality in other words which want to present something that is not real but looks real. The movie “A Piece Of Flower” raised the issue of sexual violence. The concept of editing that will be applied is to give the impression of reality through the application of the technique of editing aspects rhythmic. Aspects of the rhythmic system is in control of the length of the short shot so that an editor will be able to control the rhythm of the editing in accordance with the needs of the movie. The process of the creation of the movie is based on the existence of the issue sexual violence that happened among the next of kin, departing from the issues that formed the object creation in the form of building the impression of reality through the mockumentary movie entitled “A Piece Of Flower”. The method of creation of works of the movie “A Piece Of Flower” of course, through the stages of pre-production, production and post-production. In post production there is the process of editing or editing image around. The editing process is a process of organize, review, select and combine the “footage” of the image and sound recording production. On the work of the movie “A Piece Of Flower” the application of the technique of editing aspects of rhythmic used to build the impression of reality through the emotional emphasis of the audience. In this emphasis, emotional audience built through the application of the duration or timing. timing is a part of the rhythmic function to determine the average duration used in each shot. The formation of emotional in editing is also influenced by two types of rhythm that is the rhythm of the internal and external. With the application of the technique of editing aspects of rhythmic expected to be able to convey the concept of editing that has been designed so that the messages in the movie can be delivered.